2014
DOI: 10.5152/ucd.2014.2764
|View full text |Cite
|
Sign up to set email alerts
|

The approach of general surgeons to the use of vessel sealing device in thyroid surgery

Abstract: Objective: Vascular sealing devices (VSD) can be safely used in thyroid surgery. The purpose of this survey was to investigate general surgeons' approach to the use of VSD in thyroid surgery in Turkey. Material and Methods:A questionnaire containing 10 items was prepared and announced via the Dialogue in Endocrinology Society website. The results were then analyzed.Results: Fifty surgeons (65.8%) stated that they always use VSD, 20 (26.3%) stated that they sometimes use these devices and six (7.9%) declared th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Fundamental changes in the approaches of surgeons to vascular bleeding control have occurred especially due to new vessel sealing devices, which were introduced in the last decade. It has been reported that the endurance of these devices are equal to that of clips and knots if the devices were used in appropriate capacity (4,9) In a questionnaire study on thyroid surgery and vessel sealing devices performed in our country, it was found that these devices are used in 65% of all thyroidectomy operations. In the same study, 47% of the surgeons reported that they use ligation in every case, while 55% stated that upper pole vessels must be ligated at least once (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fundamental changes in the approaches of surgeons to vascular bleeding control have occurred especially due to new vessel sealing devices, which were introduced in the last decade. It has been reported that the endurance of these devices are equal to that of clips and knots if the devices were used in appropriate capacity (4,9) In a questionnaire study on thyroid surgery and vessel sealing devices performed in our country, it was found that these devices are used in 65% of all thyroidectomy operations. In the same study, 47% of the surgeons reported that they use ligation in every case, while 55% stated that upper pole vessels must be ligated at least once (4).…”
Section: Discussionmentioning
confidence: 99%
“…Many surgeons prefer conventional suturing. As it is known, sutures are foreign bodies for the body and may cause a reaction, which is more common especially with non-absorbable sutures (1,4,5).…”
Section: Introductionmentioning
confidence: 99%